2021
DOI: 10.1007/s13384-021-00433-z
|View full text |Cite
|
Sign up to set email alerts
|

Feeling for the Anthropocene: Placestories of living justice

Abstract: In this written version of the 2019 Radford Lecture, I address the challenges of teaching and learning about ourselves and others-human and more-than-human others-at this moment of global precarity. In Part 1, I analyse emotions in the Anthropocene through the lens of carnivalesque placestories. I conclude that we need to shift to a relational ontology and aesthetic sensibility based on kinship with the more-than-human. Part 2 explores pedagogies of love and enchantment and presents specific cases suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…This result revealed on how care, love and solidarity are crucial, as these bring kinship and create meaningfulness in individuals' lifeworlds, as well as bring focus on othercentredness (Lynch, 2007;Lynch et al, 2021), thus directing ethical concern outside the individual. Like Renshaw's (2021) recent work, the results of this study indicated the importance of opportunities to acknowledge love, care and solidarity within environmental sustainability and environmental education as crucial approaches and 'building blocks' for how to approach the environment, other species and each other.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This result revealed on how care, love and solidarity are crucial, as these bring kinship and create meaningfulness in individuals' lifeworlds, as well as bring focus on othercentredness (Lynch, 2007;Lynch et al, 2021), thus directing ethical concern outside the individual. Like Renshaw's (2021) recent work, the results of this study indicated the importance of opportunities to acknowledge love, care and solidarity within environmental sustainability and environmental education as crucial approaches and 'building blocks' for how to approach the environment, other species and each other.…”
Section: Discussionsupporting
confidence: 60%
“…This part of his storying highlights how his ethical concerns are generated by his care and love of trees. Liam's emotionally entangled spatial and embodied experiences led to finding importance in protecting and defending the trees in the local forests (Renshaw, 2021). During the first workshop, Liam thus temporarily moved from experiences from earlier in his childhood, then back to the classroom context and further into his future pictures that connected to the Lion tree (see episodes L.2-3 in Figure 2).…”
Section: The Story Of the Lion Tree As A Turning Point In Digital Sto...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is impossible to overstate the necessity of schools around the globe, but especially in advanced nations such as the United Kingdom, to become levers of positive action within the climate crisis. As suppliers of cultural narratives (Facer, 2019; Renshaw, 2021) and as promoters of critical reading and analytic reading skills (Zengilowski et al, 2021), literacy teachers have a powerful role to play should we choose to play it. This research suggests that to do so, preservice teachers need preparation to evaluate the credibility of authors of fictional children's literature.…”
Section: Discussionmentioning
confidence: 99%
“…One reason to centre climate change narratives in literacy education is that the stories we carry about the future hold value as imaginative tools and cultural artefacts (Renshaw, 2021). In the United States, also a member nation of OECD, the National Council for Teachers of English (NCTE) has passed a resolution declaring that, “addressing climate change demands the involvement of English language arts teachers … students need to explore images, texts, ideas, perspectives, and issues; need to empathize with victims of climate change; and need to imagine consequences and possibilities” (NCTE, 2019, n.p.).…”
Section: Introductionmentioning
confidence: 99%